(untitled) (Research, Society and Development, 2021)
The pandemic situation established in the world due to the emergence of diseases and their injuries resulting from COVID-19 brought several paradigm shifts in the individual and collective sphere of societies, which suddenly and unexpectedly found themselves facing a new reality. Given the above, this research has as its main objective to analyze the safety of exposure to occupational risks of the various health workers who work directly against the COVID-19 pandemic in the health instance in Rio de Janeiro. As specific objectives: it will measure its effect and thus compare it with the foundation offered by the Health Management, aiming, in this way, to demonstrate the relevance of prevention and promotion of the health of the health worker in the face of the COVID-19 pandemic, which consequently it will contribute to social health and regional development. This research is quantitative in nature and according to taxonomy, in relation to the purposes, it is a descriptive research, the technique used was the snowball. The instrument chosen for this research was a questionnaire created through Google Forms. The survey reveals that 20% of the participants were not presented with the safety protocols to carry out their functional activities, and that the safety protocols are not being satisfactorily implemented in the professional practice through the institutions, as it also points out a significant number of participants who did not receive medical support, or other support from the company due to exposure to COVID-19.